DAYA ANTELMINTIK EKSTRAK ETANOL DAUN MENGKUDU (Morinda citrifolia L.) TERHADAP CACING Ascaridia galli SECARA In Vitro DAN PROFIL KLTNYA - riyanta aribawa; anis wihdayanti; mustofa mustofa (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2008)
ABSTRACTPeople used noni leaf (Morinda citrifolia L.)for medication many kinds disease, one of as anthelmintic. Worm infection most generally in the world, especially in growing countries including indonesia. To prove the truth were efficacious noni leaf as anthelmintic has been research anthelmintic capability ethanol extract of noni leaf on the worm Ascaridia galli on in vitro. This research has done by using Lamson and Brown method submerges that has been modified. Research using 270 of worms A. galli female, that devided into 9 groups, that’s 4 groups treatment with ethanol extract of noni leaf in consentration of 20 mg/mL, 30 mg/mL, 40 mg/mL and 50 mg/mL, 4 groups positive control (citrate piperazin) consentration 2 mg/mL, 4 mg/mL, 6 mg/mL dan 8mg/mL and I group negative control (NaCl 9 mg/mL) each group consist of 6 petri disc (each petri disc contain 5 of worms and 25 ml solution). Anthelmintic capability showed with worm mortality time that’s observed every 2 hours and LC50 that needed consentration to wipe out 50% of worm. The result of this research shown rates worm mortality time after submerges with ethanol extract of noni leaf consentration 20 mg/mL, 30 mg/mL, 40 mg/mL and 50 mg/mL as hight as 48,00 ± 1,79 ; 44,33 ± 1,51; 40,33 ± 1,51; 36,00 ± 2,53 (hours). But after submerges with citrate piperazin 4 mg/mL is 34,33 ± 1,51 (hours). LC50 after submerges ethanol axtract of noni leaf is 50,21 mg/mL and after submerges 2,27 mg/mL. The result of the observed Thin Layer Chromatography (TLC) shown ethanol extract of noni leaf containes compounds from flavonoid and fenol. Based on result of the reseach would be concluded that ethanol extract of noni leaf contain compounds that calculate have anthelmintic activity, possibilty that’s compounds is flavonoid and fenol. Keyword : Morinda citifolia L. , anthelmintic, submerges of Lamson and Brown.